2000
DOI: 10.1116/1.1303857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gap states on scanning tunneling spectra observed on (110)- and (001)-oriented clean surfaces and ultrathin Si layer covered surfaces of GaAs prepared by molecular beam epitaxy

Abstract: Articles you may be interested inSpin-polarized scanning tunneling microscopy and spectroscopy study of c ( 2 × 2 ) reconstructed Cr(001) thin film surfaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…The conductance gap anomaly in STS spectra was reported previously on GaAs (001) surfaces [1,[3][4][5]. In this study, it was found that this anomaly also takes place on AlGaAs and InGaAs surfaces.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The conductance gap anomaly in STS spectra was reported previously on GaAs (001) surfaces [1,[3][4][5]. In this study, it was found that this anomaly also takes place on AlGaAs and InGaAs surfaces.…”
Section: Discussionsupporting
confidence: 57%
“…As an alternative model, we have proposed recently a new model based on where highly localized charging of the surface states due to direct supply or removal of electrons by the STM tip changes locally the magnitude of the surface band bending, and causes the observed anomaly [4,5]. Here, we assumed that the occupancy of the surface states is dynamically determined by the tip Fermi level rather the semiconductor bulk Fermi level due to fast tunneling into surface states and slow thermal escape of electrons from surface states.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations